Both 3,5-Diiodo-L-Thyronine and 3,5,3′-Triiodo-L-Thyronine Prevent Short-term Hepatic Lipid Accumulation via Distinct Mechanisms in Rats Being Fed a High-Fat Diet - Senese, Rosalba; Cioffi, Federica; de Lange, Pieter; Leanza, Cristina; Iannucci, Liliana F.; Silvestri, Elena; Moreno, Maria; Lombardi, Assunta; Goglia, Fernando; Lanni, Antonia (Frontiers in Physiology, 2017)
3,3’,5-triiodo-L-thyronine (T3) improves hepatic lipid accumulation by increasing lipid catabolism but it also increases lipogenesis, which at first glance appears contradictory. Recent studies have shown that 3,5-diiodothyronine (T2), a natural thyroid hormone derivative, also has the capacity to stimulate hepatic lipid catabolism, however, little is known about its possible effects on lipogenic gene expression. Because genes classically involved in hepatic lipogenesis such as SPOT14, acetyl-CoA-carboxylase (ACC), and fatty acid synthase (FAS) contain thyroid hormone response elements (TREs), we studied their transcriptional regulation, focusing on TRE-mediated effects of T3 compared to T2 in rats receiving high-fat diet (HFD) for one week. HFD rats showed a marked lipid accumulation in the liver, which was significantly reduced upon simultaneous administration of either T3 or T2 with the diet. When administered to HFD rats, T2, in contrast with T3, markedly downregulated the expression of the above-mentioned genes. T2 downregulated expression of the transcription factors carbohydrate-response element-binding protein (ChREBP) and sterol regulatory element binding protein-1c (SREBP-1c) involved in activation of transcription of these genes, which explains the suppressed expression of their target genes involved in lipogenesis. T3, however, did not repress expression of the TRE-containing ChREBP gene but repressed SREBP-1c expression. Despite suppression of SREBP-1c expression by T3 (which can be explained by the presence of nTRE in its promoter), the target genes were not suppressed, but normalized to HFD reference levels or even upregulated (ACC), partly due to the presence of TREs on the promoters of these genes and partly to the lack of suppression of ChREBP. Thus, T2 and T3 probably act by different molecular mechanisms to achieve inhibition of hepatic lipid accumulation.